PENGARUH REFORMASI ADMINITRASI PERPAJAKAN DAN PENGETAHUAN PERPAJAKAN TERHADAP TINGKAT KEPATUHAN PENGUSAHA KENA PAJAK (Studi Empiris Pada Kantor Pelayanan Pajak Pratama Jayapura) - Wilberth Aiwoy; Otniel Safkaur; Aaron M. A. Simanjuntak (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2021)
This study aims to analyze the effect of tax administration reform and tax knowledge on the compliance of Taxable Entrepreneurs in paying taxes at KPP Pratama Jayapura. This type of research data was obtained from primary data where questionnaires were distributed directly to Taxable Entrepreneurs while maintaining the COVID-19 health protocol. This study is a quantitative study with a sample of 100 Taxable Entrepreneurs registered at KPP Pratama Jayapura. The method used to determine the sample in this study is accidental sampling. The analysis technique used in this research is validity and reliability test, classical assumption test, multiple linear regression test and hypothesis. The results showed that simultaneously improving tax administration and knowledge of taxation together had a significant effect on the compliance of Taxable Entrepreneurs at KPP Pratama Jayapura.